Frequency of five cardiovascular/hemostatic entities as primary manifestations of SARS-CoV-2 infection: Results of the UMC-19-S2. (1st May 2021) - Miró, Òscar; Llorens, Pere; Jiménez, Sònia; Piñera, Pascual; Burillo-Putze, Guillermo; Martín, Alfonso; Martín-Sánchez, Francisco Javier; González del Castillo, Juan; ,; Miró, Òscar; Jiménez, Sònia; del Castillo, Juan González; et al.
Highlights: Several cardiovascular/hemostatic disturbances haves been reported in patients with COVID-19, but the real frequency and their potential association with the pathogenic mechanisms of SARS-CoV-19 still remain to be defined. We investigated the relative frequency of acute coronary syndrome, deep venous thrombosis, pulmonary embolism, stroke and upper gastrointestinal bleeding in COVID patents attending emergency departments (EDs), before hospitalization and compared them with frequencies in the general ED population attending 50 Spanish EDs. We found that the risk of pulmonary embolism is clearly increased in COVID patients, with an OR of 4.53 with respect to non-COVID patients (95% confidence interval 4.03- 5.10). Additionally, the diagnosis of pulmonary embolism was 2 fold more frequent among ED comers in 2020 compared to 2019, suggesting a SARS-CoV-2 role in such increment of cases.. The remaining entities studied were not found to be unequivocally increased in the present study and need further investigation.